A Photovoice Inquiry Into the Impacts of a Subsidized CSA Program on Participants' Health. (October 2022) - Martin, Allea; Coplen, Amy; Lubowicki, Lauren; Izumi, Betty
Although consumption of fruits and vegetables is associated with reduced risk of disease, many Americans do not eat the recommended quantity or variety. This is especially true for low-income populations, who may face significant barriers to accessing fresh produce, including cost. Community-supported agriculture (CSA) Partnerships for Health is a subsidized community-supported agriculture program designed to reduce barriers to accessing fresh produce in a low-income population. This Photovoice study gave participants ( n = 28) an opportunity to take photos representing how the program affects their lives. The aim was to understand the program's impact from the perspective of CSA members. Participants had 2 to 4 weeks to take photographs, and then selected a few to discuss during a subsequent focus group. Through this discussion, we learned that participants see the program as (a) supporting positive changes to their physical and social health and (b) facilitating learning about new foods, cooking, and agriculture. The study suggests that a reduced-cost CSA membership that incorporates cooking education supports participants' ability to try new foods, build skills, and improve health outcomes.